Disrupting EDEM3‐induced M2‐like macrophage trafficking by glucose restriction overcomes resistance to PD‐1/PD‐L1 blockade - Shaoyong Peng; Minshan Wu; Qian Yan; Gaopo Xu; Yumo Xie; Guannan Tang; Jinxin Lin; Zixu Yuan; Xiaoxia Liang; Ze Yuan; Jingrong Weng; Liangliang Bai; et al. (Clinical and Translational Medicine, 2025)
Abstract Background Immunotherapy is beneficial for some colorectal cancer (CRC) patients, but immunosuppressive networks limit its effectiveness. Cancer‐associatedfibroblasts (CAFs) are significant in immune escape and resistance toimmunotherapy, emphasizing the urgent need for new treatment strategies. Methods Flow cytometric, Western blotting, proteomics analysis, analysis of public database data, genetically modified cell line models, T cell coculture, crystal violetstaining, ELISA, metabonomic and clinical tumour samples were conducted to assess the role of EDEM3 in immune escape and itsmolecular mechanisms. We evaluated theeffects of FMD plus 2‐DG on antitumour immunity using multipleximmunofluorescence, flow cytometry, cytokine profiling, TUNEL assays, xenografttumours, and in vivo studies. Results We show thatCAFs upregulate PD‐L1 glycosylation and contribute to immune evasion byglycosyltransferase EDEM3. Additionally, EDEM3 plays a role in tumour immunityduring tumour progression. However, the EDEM3‐mediated upregulation of PD‐L1 expression underpins PD‐1/PD‐L1 blockade resistance in vivo. This finding contradictsthe previous trend that positive PD‐L1 expression indicates a strong responseto PD‐1/PD‐L1 blockade. Mechanistically, high‐EDEM3 expression facilitates M2‐like This finding contradictsthe previous trend that positive PD‐L1 expression indicates a strong responseto PD‐1/PD‐L1 blockade.Mechanistically, polarizationand chemotactic migration of macrophages, which are enriched in theperipheral region of tumours compared to thecore region, precluding access of CD8+ T cells to tumourfoci. Furthermore, we EDEM3 predominantly activates the recruited M2‐like macrophagesvia a glucose metabolism‐dependent mechanism. Manipulationof glucose utilization by a fasting‐mimicking diet(FMD) plus 2‐DG treatmentsynergistically with PD‐1 antibody elicits potent antitumour activity byeffectively decreasing tumour glycosylated PD‐L1 expression, augmenting the CD8+effector T cell infiltration and activation while concurrently reducing the infiltration.TheCAFs‐EDEM3‐M2‐like macrophage axis plays a critical role in promotingimmunotherapy resistance. infiltration.TheCAFs‐EDEM3‐M2‐like macrophage axis plays a critical role in promotingimmunotherapy resistance. Conclusions Our study suggests that blocking EDEM3‐induced M2‐like macro phage trafficking by FMD plus 2‐DG is a promising and effective strategy to overcomeresistance to checkpoint blockade therapy offeringhope for improved treatment outcomes. Key points Cancer‐associated fibroblasts (CAFs) can enhance PD‐L1 glycosylation through the glycosyltransferase EDEM3, contributing to immune evasion during tumour progression. EDEM3 predominantly activates the recruit M2‐like macrophages via a glucose metabolism‐dependent mechanism. Blocking glucose utilization antagonizes recruiting and polarizing M2‐like macrophages synergistically with PD‐1 antibody to improve anticancer immunity.